2013
DOI: 10.3329/ijarit.v1i1-2.13931
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Economic Suitability of Three Fast Growing Broiler Strains Raised Under Farming Condition in Bangladesh

Abstract: The performance and profitability of three commercial broiler strains reared under farming system were investigated in this study. Day-old broiler chicks (n=156) of three different commercial strains (Hubbard classic, Cobb-500 and MPK) were assigned to three treatment groups in a completely randomized block design, each treatment replicated four times, 13 birds per replicate. The birds were reared from d1 to 35 days of age with similar housing, feeding and environmental management condition. Regarding to all p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 17 publications
2
5
0
Order By: Relevance
“…Similarly, at the age of 42 days, the FCR was best in Vencobb-400 (2.58) followed by 2.61 in Hubbard and 2.68 in Vencobb, respectively.Similar results were shown by Zaman et al (2015) who found the significant difference in FCR among the three broiler strains during summer season. These findings were also supported the observations of Hossain et al (2011) andSudarman et al (2011) that there exist significant difference in FCR among different broiler strains. The improved FCR of Vencobb-400 chicks indicates that this strain is more efficient in converting feed to meat more rapidly than in other strains.…”
Section: Feed Conversion Ratio (Fcr)supporting
confidence: 81%
“…Similarly, at the age of 42 days, the FCR was best in Vencobb-400 (2.58) followed by 2.61 in Hubbard and 2.68 in Vencobb, respectively.Similar results were shown by Zaman et al (2015) who found the significant difference in FCR among the three broiler strains during summer season. These findings were also supported the observations of Hossain et al (2011) andSudarman et al (2011) that there exist significant difference in FCR among different broiler strains. The improved FCR of Vencobb-400 chicks indicates that this strain is more efficient in converting feed to meat more rapidly than in other strains.…”
Section: Feed Conversion Ratio (Fcr)supporting
confidence: 81%
“…The birds that reared under closed house has received the significant effect with meatiness except the ratio breast muscle to the bone weight, the meatiness of the thigh and the breast. The researchers (Kurcubic et al, 2006); (Hossain et al, 2011) and (Adebiyi and Adu 2011) also agreed with the current research that the housing condition affected to the performances of the broilers.…”
Section: Effect Of the Housing Condition On The Meatiness Of The Broisupporting
confidence: 67%
“…When considering the previous studies (Adebiyi and Adu, 2011); (Traits et al, 2012) ( Hossain et al, 2011) and (Almasi et al, 2012) those were agreed that strain had significantly affected to the yield of the broiler production. It means the HC has more flesh, more edible part when comparing with inedible part, as well as the live weight and the bone weight.…”
Section: Effect Of the Housing Condition On The Meatiness Of The Broimentioning
confidence: 99%
See 1 more Smart Citation
“…The poultry industry is recognized as the most popular emerging industry in the world [1,2,3]. Chicken meat represents a good and cheap protein source compared to red meat.…”
Section: Introductionmentioning
confidence: 99%